Parameters Sensitivity Analysis of the Minimalist-designed Linearized Optical Frequency Discriminator for Microwave Photonics Link - Dingel, Benjamin (Archīum Ateneo, 2022)
We present a comprehensive parameters sensitivity analysis of the minimalist-design frequency discriminator, FD filter involving three parameters namely, (i) the back reflection coefficient “ $b$ ”, (ii) mirror reflectance “ $a$ ”, and (iii) the split-power ratio of the Y-combiner “ $r$ ”. We demonstrated that the measured linearity (bandwidth utilization, BWU and Normalized Deviation, ND) are negatively impacted by the increase in parameters b and r, but can be compensated by decreasing the value of the mirror reflectivity “ $a$ ”.